Fabrication of regenerated grating using carbon dioxide laser - Lim, K.S. (2015)
Grating regeneration using CO2 laser has been demonstrated. Bragg wavelength redshifts as the irradiated laser power is elevated. The grating reflectivity begins to decay as the induced temperature is approaching the erasure temperature. The grating is completely erased and regenerated afterward.